Straightening machine preventive maintenance intervention plan based on AHP: a case study in a steel company in Brazil - De Oliveira, Ualison Rébula; de Souza, Hilda Anatiely Donato; Menezes, Carlos Augusto Gabriel [UNESP]; Rocha, Henrique Martins (Springer Nature, 2023)
Equipment failure and production shortfalls can cause significant impacts on companies. Preventive maintenance can potentially increase equipment reliability and availability, helping companies achieve their corporate goals while reducing operation and maintenance costs. However, determining the optimal interval between maintenance interventions involves balancing various factors such as maintenance costs, equipment availability, risk of failures, and the need for corrective maintenance, as well as potential operational and financial impacts. Under this context, this paper aims to define the interval between preventive maintenance interventions for a key production equipment in a steel company located in Southeast region of Brazil. Upon documental analysis and interviews with experts, an AHP was applied to hierarchize the maintenance periodicity, based on the following criteria: part replacement based on service life, downtime hours for preventive maintenance, equipment reliability, and cost of materials and labour. A biweekly preventive maintenance periodicity was identified as the most adequate for the analysed device. An implementation plan was approved and preliminary results indicate no availability deterioration, while maintenance costs are below historical average.
Keywords: Analytic Hierarchy process; Equipment availability; Maintenance plans; Multicriteria decision; Periodicity; Preventive maintenance